Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Plant neighbour identity matters to belowground interactions under controlled conditions. - Armas, Cristina; Pugnaire, Francisco Ignacio (PloS one, 2011)
Root competition is an almost ubiquitous feature of plant communities with profound effects on their structure and composition. Far beyond the traditional view that plants interact mainly through resource depletion (exploitation competition), roots are known to be able to interact with their environment using a large variety of mechanisms that may inhibit or enhance access of other roots to the resource or affect plant growth (contest interactions). However, an extensive analysis on how these contest root interactions may affect species interaction abilities is almost lacking.
The following values have no corresponding Zotero field: accession-num: 22114696
Keywords: biomass; citation; Ecosystem; Environment; Plant Development; Plant Roots; Plant Roots: growth & development; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

The influence of linear elements on plant species diversity of Mediterranean rural landscapes: assessment of different indices and statistical approaches. - García del Barrio, J M; Ortega, M; Vázquez De la Cueva, A; Elena-Rosselló, R (Environmental monitoring and assessment, 2006)
This paper mainly aims to study the linear element influence on the estimation of vascular plant species diversity in five Mediterranean landscapes modeled as land cover patch mosaics. These landscapes have several core habitats and a different set of linear elements--habitat edges or ecotones, roads or railways, rivers, streams and hedgerows on farm land--whose plant composition were examined. Secondly, it aims to check plant diversity estimation in Mediterranean landscapes using parametric and non-parametric procedures, with two indices: Species richness and Shannon index. Land cover types and landscape linear elements were identified from aerial photographs. Their spatial information was processed using GIS techniques. Field plots were selected using a stratified sampling design according to relieve and tree density of each habitat type. A 50x20 m2 multi-scale sampling plot was designed for the core habitats and across the main landscape linear elements. Richness and diversity of plant species were estimated by comparing the observed field data to ICE (Incidence-based Coverage Estimator) and ACE (Abundance-based Coverage Estimator) non-parametric estimators. The species density, percentage of unique species, and alpha diversity per plot were significantly higher (p < 0.05) in linear elements than in core habitats. ICE estimate of number of species was 32% higher than of ACE estimate, which did not differ significantly from the observed values. Accumulated species richness in core habitats together with linear elements, were significantly higher than those recorded only in the core habitats in all the landscapes. Conversely, Shannon diversity index did not show significant differences.
Keywords: Biodiversity; Conservation of Natural Resources; Conservation of Natural Resources: statistics & nu; core habitat; diversity; Ecosystem; ecotones; Environmental Monitoring; Environmental Monitoring: methods; Geography; landscape; linear elements; Mediterranean; Mediterranean Region; Plant Development; Poaceae; Poaceae: growth & development; Shannon index; Species richness; Species Specificity; Trees; Trees: growth & development